2017
DOI: 10.1038/srep41334
|View full text |Cite
|
Sign up to set email alerts
|

Imorin: a sexual attractiveness pheromone in female red-bellied newts (Cynops pyrrhogaster)

Abstract: The male red-bellied newt (Cynops pyrrhogaster) approaches the female’s cloaca prior to performing any courtship behaviour, as if he is using some released substance to gauge whether she is sexually receptive. Therefore, we investigated whether such a female sexual attractiveness pheromone exists. We found that a tripeptide with amino acid sequence Ala-Glu-Phe is secreted by the ciliary cells in the epithelium of the proximal portion of the oviduct of sexually developed newts and confirmed that this is the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Reproductive isolation, which restricts gene flow between sympatric populations, is one of the key mechanisms of speciation [1]. Mating between individuals of closely related species is prevented by a prezygotic barrier, which is mainly caused by changes in signals that enable individuals to appropriately recognize the opposite sex: for example, pheromones in insects [2,3] and amphibians [4,5], body color in fish [6], and song in birds [7]. Although such reproductive isolation has been frequently studied in higher organisms, far less is known in fungi [8].…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive isolation, which restricts gene flow between sympatric populations, is one of the key mechanisms of speciation [1]. Mating between individuals of closely related species is prevented by a prezygotic barrier, which is mainly caused by changes in signals that enable individuals to appropriately recognize the opposite sex: for example, pheromones in insects [2,3] and amphibians [4,5], body color in fish [6], and song in birds [7]. Although such reproductive isolation has been frequently studied in higher organisms, far less is known in fungi [8].…”
Section: Introductionmentioning
confidence: 99%
“…Sex pheromones can be produced de novo in specialized glands or tissues. For instance, most male lizards have femoral glands secreting both lipophilic and proteinaceous compounds, while the sex peptide pheromones of female newts are secreted by abdominal glands (see e.g., Martín & López, 2010;Nakada et al, 2017). Odour communication seems to play an important role for reproduction also in birds, with uropygial glands producing oily secretions likely used for sex recognition in most bird species (Caro et al, 2015).…”
Section: Sex Pheromones: Chemical Nature and Biosynthesismentioning
confidence: 99%
“…Newts have other unique biological properties such as large genome sizes (Elewa et al, 2017), tumor-resistance (Ingram, 1972;Okamoto, 1987), physiological polyspermy in their fertilization (Picheral, 1977;Charbonneau et al, 1983;Iwao, 2012), and sexual pheromones for mating-behavior (Nakada et al, 2017). Furthermore, Mouchet and other groups showed that newts are useful animals for toxicity testing of chemical compounds (Mouchet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%